Boosting Development through Population Growth in the Greek Periphery: The Case of Rodopi, Greece - Tsertekidis, Georgios; Polyzoidis, Periklis (HAPSc Policy Briefs Series, 2024)
Rodopi (Rhodope), a peripheral region in northeastern Greece, faces significant demographic challenges characterized by population decline, aging, and negative net migration. This policy brief explores these challenges and proposes a set of policy recommendations to revitalize Rodopi’s demographics and stimulate regional development. The recommendations focus on attracting and retaining young people, supporting families, and promoting economic opportunities.